2021
DOI: 10.31234/osf.io/hn7us
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Longitudinal change in adolescent depression and anxiety symptoms from before to during the COVID-19 pandemic: A collaborative of 12 samples from 3 countries

Abstract: The study aimed to examine changes in depression and anxiety symptoms from before to during the first six months of the COVID-19 pandemic in a large, diverse, international sample of 1,339 adolescents (9-18 years, 59% female). We also examined if age, race/ethnicity, disease burden, or strictness of government restrictions moderated change in symptoms. Data from 12 longitudinal studies (10 U.S., 1 Netherlands, 1 Peru) were combined. Linear mixed effect models showed that depression symptoms increased significa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
90
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(104 citation statements)
references
References 28 publications
9
90
5
Order By: Relevance
“…Beyond adults' depression, depression among middle school students has been given attention in the literature as many have suffered from depression due to school life or relationships with their parents (Greenberger and Chen, 1996;Sheeber et al, 1997;Tucker et al, 2003;Sajjadi et al, 2013;Yun et al, 2019). Since COVID-19, middle schoolers have reported more frequent depression and higher levels of depression (Barendse et al, 2021;Magson et al, 2021;Ravens-Sieberer et al, 2021). As COVID-19 has changed various aspects of our lives, there may be complicated relationships influencing middle school students' depression.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond adults' depression, depression among middle school students has been given attention in the literature as many have suffered from depression due to school life or relationships with their parents (Greenberger and Chen, 1996;Sheeber et al, 1997;Tucker et al, 2003;Sajjadi et al, 2013;Yun et al, 2019). Since COVID-19, middle schoolers have reported more frequent depression and higher levels of depression (Barendse et al, 2021;Magson et al, 2021;Ravens-Sieberer et al, 2021). As COVID-19 has changed various aspects of our lives, there may be complicated relationships influencing middle school students' depression.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, however, the COVID-19 pandemic has been more consequential for some adolescents than for others (6,7,47). Elucidating relevant aspects of neurobiological functioning could increase our understanding of individual differences in risk versus resilience to mental health problems during the pandemic (8-10).…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents generally are at increased risk for stress-related mental health problems such as depression (4,5) and, therefore, may be particularly vulnerable during the COVID-19 pandemic. Indeed, depressive symptoms in adolescents appear to be increasing during this period (6,7). It is almost certain that some adolescents are more vulnerable than others to experiencing difficulties during the COVID-19 pandemic, differences that have been found to be indexed by neurobiological and physiological markers (8)(9)(10).…”
mentioning
confidence: 99%
“…Emotional symptoms increased in preadolescents, but slightly decreased for adolescents MENTAL HEALTH OF AUSTRALIAN YOUTH DURING COVID-19 4 (Waite et al, 2021). Another non-peer-reviewed study (predominantly US) found that selfreported depressive symptoms, but not anxiety symptoms, had increased among adolescents over the first six months of the pandemic (Barendse et al, 2021). Together, these studies show that child and adolescent mental health symptoms have worsened during the pandemic.…”
Section: Mental Health Symptoms In Children and Adolescents During Covid-19 In Australiamentioning
confidence: 92%